2018
DOI: 10.1111/cen.13885
|View full text |Cite
|
Sign up to set email alerts
|

A 5α‐reductase (SRD5A2) polymorphism is associated with serum testosterone and sex hormone–binding globulin in men, while aromatase (CYP19A1) polymorphisms are associated with oestradiol and luteinizing hormone reciprocally

Abstract: Summary Context Pituitary luteinizing hormone (LH) stimulates testicular production of testosterone (T) which is metabolized to dihydrotestosterone (DHT) by 5α‐reductase and to oestradiol (E2) by aromatase. How the activity of population variants in these enzymes impacts on gonadal function is unclear. We examined whether polymorphisms in 5α‐reductase (SRD5A2) and aromatase (CYP19A1) genes predict circulating sex hormone concentrations. Design Cross‐sectional analysis of 1865 community‐dwelling men aged 50.4 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In addition, rs9282858 was also shown to predict serum testosterone and SHBG levels in adult men, where GA carriers had higher serum testosterone and SHBG levels than GG carriers. 46 This result corresponds to our findings in ASD boys, where GG carriers showed stronger RRBs and stronger RRBs were shown to be related to lower SHBG levels.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, rs9282858 was also shown to predict serum testosterone and SHBG levels in adult men, where GA carriers had higher serum testosterone and SHBG levels than GG carriers. 46 This result corresponds to our findings in ASD boys, where GG carriers showed stronger RRBs and stronger RRBs were shown to be related to lower SHBG levels.…”
Section: Discussionsupporting
confidence: 91%
“…The result of the genetic analysis raises the question of the possible causal effect of these polymorphisms in lowering aromatase function and, consequently, serum E 2 . Recently, several genetic studies have demonstrated an association between some aromatase polymorphisms and lower levels of serum E 2 in men ( 20 , 21 , 22 ). Even though none of the SNPs and/or polymorphisms found in our patient and his cousin are known to be related to aromatase dysfunction, it is possible that one or more of them may be at the basis of their observed low serum E 2 .…”
Section: Discussionmentioning
confidence: 99%